1971
DOI: 10.1002/pssb.2220450208
|View full text |Cite
|
Sign up to set email alerts
|

Electroreflectance Spectra and Energy Band Structure of CdSnP2

Abstract: E. I. LEONOV (c), V. M. ORLOV (c), V. A. CHALDYSHEV (b), and A. SILEIKA (a)The electroreflectance spectra of CdSnP, chalcopyrite single crystals have been investigated in the spectral region 1.0 to 4.7 eV at room temperature using polarized light. The electroreflectance structure in the region of the fundamental absorption edge and its polarization dependence are found to be in good agreement with the relative location of the valence bands earlier predicted theoretically. A great number of electroreflectance p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

1972
1972
1980
1980

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Following this model the peaks at higher energies are attributed only to optical transitions having been direct in sphalerite and responsible for the main structures El, Ei, and E, in the optical spectra of AI'IB" compounds. The richer structures in optical spectra of A1lBIVCY compounds are mainly caused by the splittings of the corresponding bands under the influence of the asymmetrical part of the crystal potential due 2, The notation of peaks is the same as for the other AIIBIVCT crystals [22] (the weak peak E, is absent in the thermoreflectance spectrum of ZnGePJ. .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following this model the peaks at higher energies are attributed only to optical transitions having been direct in sphalerite and responsible for the main structures El, Ei, and E, in the optical spectra of AI'IB" compounds. The richer structures in optical spectra of A1lBIVCY compounds are mainly caused by the splittings of the corresponding bands under the influence of the asymmetrical part of the crystal potential due 2, The notation of peaks is the same as for the other AIIBIVCT crystals [22] (the weak peak E, is absent in the thermoreflectance spectrum of ZnGePJ. .…”
Section: Resultsmentioning
confidence: 99%
“…The energies and pronounced polarizations of the thermoreflectance peaks El to and Ee to of ZnGeP, are listed in Table 1. The interpretation of thermoreflectance peaks a t higher energies has been done according to the model [22] based on energy band structure calculations and taking into account the changes of the band structure passing from the AIIIBV compound to its ternary analogue A1IBIVC:. Following this model the peaks at higher energies are attributed only to optical transitions having been direct in sphalerite and responsible for the main structures El, Ei, and E, in the optical spectra of AI'IB" compounds.…”
Section: Resultsmentioning
confidence: 99%
“…As such effects may be even more important in predicting properties of "superheavy" nuclei, it is desirable that they be understood in the experimentally accessible regions of the periodic table. A recent Letter of McGowan et al 3 reported on such…”
mentioning
confidence: 98%
“…Kavaliauskas et al 3 have proposed that these four transitions in CdSnP 2 are centered about the N point of the chalcopyrite Brillouin zone. Because of the ordering of the cations, the chalcopyrite Brillouin zone has one quarter of the volume of the zinc-blende Brillouin zone.…”
mentioning
confidence: 99%
See 1 more Smart Citation